Genetically confirmed chronic granulomatous disease in a Kenyan child: case report - Marangu-Boore, Diana; Kambuni, Fred; Onyinkwa, Mary; Ramprakash, Stalin; C.P., Raghuram; Eley, Brian; Bhattad, Sagar (Frontiers in Immunology, 2023)
Introduction: We report the first case of genetically confirmed chronic granulomatous disease (CGD) in a Kenyan child. Clinical findings: A seven-month-old male, the only child of non-consanguineous parents, presented with cough, fever, fast breathing, oral thrush and axillary lymphadenopathy ipsilateral to the Calmette-Guérin bacillus scar. He had been hospitalized five weeks prior for severe pneumonia. Plain chest radiography showed bilateral patchy airspace opacification; and chest computed tomography revealed multiple large lung nodules and left axillary lymphadenopathy. HIV ELISA was negative; tuberculin skin test positive; lymph node biopsy macroscopically caseous with granulomas seen on histology, isoniazid and rifampicin susceptible Mycobacterium tuberculosis complex isolate was detected on Hain test. First-line anti-tuberculous drugs were added to his empiric treatment comprising piperacillin-tazobactam, amikacin, co-trimoxazole and fluconazole. He was discharged after 10 days based on clinical resolution. Diagnoses, interventions and outcome: An inborn error of immunity (IEI) was considered given the recurrent fevers and atypical lung nodules. Genetic analysis revealed a hemizygous pathogenic variant on CYBB in keeping with X-linked CGD. The child’s fevers recurred two weeks post-discharge but completely resolved on prophylactic itraconazole and cotrimoxazole. He underwent a successful haplo-identical haematopoeitic stem cell transplantation at an experienced centre in India with his father as the donor; and is currently doing well on post-transplant follow-up. Conclusion: Genetic testing is relatively accessible and cost-effective for the diagnosis of IEI in low-and-middle-income countries. Expert multi-disciplinary collaboration is key for successful outcomes.